Development of a generic high-throughput screening assay for profiling snake venom protease activity after high-resolution chromatographic fractionation. (30th April 2020) - Neumann, Coleen; Slagboom, Julien; Somsen, Govert W.; Vonk, Freek; Casewell, Nicholas R.; Cardoso, Carmen L.; Kool, Jeroen
Abstract: Snakebites cause upwards of 1.8 million envenomings, 138, 000 deaths and 500, 000 cases of long term morbidity each year. Viper snake venoms (family Viperidae) generally contain a high proportion of proteases which can cause devastating effects such as hemorrhage, coagulopathy, edema, necrosis, and severe pain, in envenomed victims. In this study, analytical techniques were combined with enzymatic assays to develop a novel method for the detection of snake venom protease activity by using rhodamine-110-peptide substrate. In the so called at-line nanofractionation set up, crude venoms were first separated with reversed phase liquid chromatography, after which fractions were collected onto 384-well plates. Protease activity assays were then performed in the 384-well plates and bioassay chromatograms were constructed revealing protease activity. Parallel obtained UV absorbance, MS and proteomics data from a previous study facilitated toxin identification. The application of the rhodamine-110-peptide substrate assay showed significantly greater sensitivity compared to prior assays using casein-FITC as the substrate. Moreover, cross referencing UV and MS data and resulted in the detection of a number of tentative proteases suspected to exhibit protease activity, including snake venom serine proteases from Calloselasma rhodostoma and Daboia russelli venom and a snake venom metalloproteinase from the venom of Echis ocellatus. Our data demonstrate that his methodology can be a useful tool for selectively identifying snake venom proteases, and can be applied to provide a better understanding of protease-induced pathologies and the development of novel therapeutics for treating snakebite. Highlights: A post-column assay was used for assessing protease activity of snake venom toxins in crude and fractionated venoms. We developed a new and sensitive bioassay for measuring protease activity in venoms. Analytics for identifying and studying proteases in venoms were applied. A rhodamine-110 based substrate is preferred for measuring proteolytic activities in venoms.